Primary teachers' understanding of concepts of science: impact on confidence and teaching - Harlen, Wynne; Holroyd, Colin (International journal of science education, 1997)
The specification of the science to be taught in primary schools has thrown into sharper focus the matter of primary teachers' own understanding of the subject matter which has, for some time, been an area of concern. Research carried out in Scottland has explored in some depth the problems primary teachers encounter in science and technology and the extend to which these are associated with lack of confidence and/or background knowledge. The findings indicate that there are some ideas which primary teachers can quite quickly come to understand while others require more extensive in-service attention. Confidence is not only dependent on subject knowledge; teachers with low confidence employ various strategies for coping, some of which when regularly applied have a severely limiting effect on children's learning. (Autorenreferat).